IDENTIFICATION OF HEAVY METAL Cu AND Zn IN THE MEAT OF NILE TILAPIA (Oreochromis niloticus) AT IPAL BOJONGSOANG, BANDUNG REGENCY, WEST JAVA - Muhamad Seikei Shojikana; Junianto Junianto; Iskandar Iskandar; Rusky Intan Pratama (Universitas Mataram, 2024)
The Bojongsoang Wastewater Treatment Plant (IPAL) in Bojongsoang District, Bandung Regency, West Java, is a facility that processes wastewater from the city of Bandung. In the IPAL pond, there are Nile tilapia that live there and can serve as bioindicators of water quality. However, these fish are utilized by the surrounding community through fishing and netting for consumption and sale. This study aims to determine the safety level of Nile tilapia (Oreochromis niloticus) meat in the Bojongsoang IPAL based on the content of heavy metals Cu and Zn. The research was conducted from May to October 2024. The method used is a survey method with purposive sampling technique conducted at four pond sample collection locations. The accumulated heavy metal content in the Nile tilapia meat from the Bojongsoang IPAL Treatment Pond is as follows: Cu (0.1649 mg/kg, 0.1199 mg/kg, 0.1896 mg/kg, 0.1825 mg/kg) and Zn (2.5308 mg/kg, 1.9651 mg/kg, 2.3628 mg/kg, 2.5125 mg/kg). The levels of these heavy metals are still below the maximum limits set by Ditjen POM RI in 1989, indicating that the Nile tilapia meat collected from the Bojongsoang IPAL Treatment Pond is still safe for consumption based on its Cu and Zn heavy metal content.